Efficient catalytic properties of SO42−/MxOy (M = Cu, Co, Fe) catalysts for hydrogen generation by methanolysis of sodium borohydride. (29th March 2018) - Xu, Dongyan; Lai, Xinyou; Guo, Wei; Zhang, Xinyan; Wang, Chuansheng; Dai, Ping
Abstract: The SO4 2− /M x O y (M = Cu, Co, Fe) catalysts were prepared and applied to hydrogen production from methanolysis of sodium borohydride for the first time. The morphologies and properties of the as-prepared catalysts were characterized by XRD, BET, FT-IR, TEM and SEM-EDX techniques. Under our experimental conditions, SO4 2− /CuO exhibits much higher catalytic activity than those of SO4 2− /CoO and SO4 2− /Fe2 O3 catalysts and follows the order of SO4 2− /CuO > SO4 2− /CoO > SO4 2− /Fe2 O3, which is opposite to order of BET surface area, implying that the methanolysis of sodium borohydride is not a structure-sensitive reaction. It can be inferred that both acidic and metallic sites are responsible for the high catalytic performance of the SO4 2− /M x O y catalysts towards NaBH4 methanolysis. In addition, the effects of the concentrations of NaBH4 and methanol, catalyst dosage, and reaction temperature on the hydrogen generation rate have been investigated using SO4 2− /CuO as catalyst. The SO4 2− /CuO-catalyzed methanolysis reaction follows a power law, i.e . r  =  A· exp ( − 13135 /RT ) · [ NaBH 4 ] 1.01 · [ CH 3 OH ] 1.60 · [ Catalyst ] 0.52 . The apparent activation energy was calculated to be 13.13 kJ/mol. Graphical abstract: Highlights: Methanolysis of NaBH4 is effectively accelerated by using SO4 2− /M x O y (M = Cu, Co, Fe). SO4 2− /CuO exhibits higher catalytic activity than SO4 2− /CoO and SO4 2− /Fe2 O3 . Both acidic and metallic sites are responsible for the catalytic performance. A power law of NaBH4 methanolysis catalyzed by SO4 2− /CuO catalyst is obtained.